2021
DOI: 10.3390/diagnostics11020258
|View full text |Cite
|
Sign up to set email alerts
|

Significant Changes in Serum MicroRNAs after High Tibial Osteotomy in Medial Compartmental Knee Osteoarthritis: Potential Prognostic Biomarkers

Abstract: High tibial osteotomy (HTO) is an effective alternative for medial compartmental knee osteoarthritis (OA). Circulating microRNAs (miRNAs) are known to serve as OA-related biomarkers. The present study investigated the differential expression of serum miRNAs before and after HTO to identify potential miRNAs as prognostic biomarkers. miRNA-polymerase chain reaction (PCR) arrays were used to screen for miRNAs in the serum at preoperative and 6-month postoperative time points from six patients, and the differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…In line with our previous study (25), the present study observed that miR-19b-3p was higher in cartilage tissues of OA patients and elevated in IL-1bstimulated chondrocytes (OA cellular model) as well as in cartilage tissues of OA rat models. These data further validated the miR-19b-3p involvement in OA development, which might be ascribed to the effect of miR-19b-3p on regulating chondrocyte functions, ECM degradation, and inflammation (44)(45)(46). Importantly, our present study also discovered that OA-FLS exosomes promote the damage and ferroptosis of chondrocyte and cartilage via delivering miR-19b-3p in vitro and in vivo, respectively.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In line with our previous study (25), the present study observed that miR-19b-3p was higher in cartilage tissues of OA patients and elevated in IL-1bstimulated chondrocytes (OA cellular model) as well as in cartilage tissues of OA rat models. These data further validated the miR-19b-3p involvement in OA development, which might be ascribed to the effect of miR-19b-3p on regulating chondrocyte functions, ECM degradation, and inflammation (44)(45)(46). Importantly, our present study also discovered that OA-FLS exosomes promote the damage and ferroptosis of chondrocyte and cartilage via delivering miR-19b-3p in vitro and in vivo, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…miR-19b-3p is a famous noncoding RNA involved in the pathogenesis of various diseases such as cancers, skeletal abnormalities, and degenerative diseases (41)(42)(43). In the aspect of OA, miR-19b-3p is reported to regulate ECM degradation and inflammation in OA (44), and its change during/post-treatment relates to OA recovery (45). Moreover, our previous study used microarray and RT-qPCR assay to confirm that miR-19b-3p was elevated in knee OA patients compared to healthy controls, which was further revealed to be an independent risk factor for OA susceptibility (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-140-3p level has been monitored in the serum from OA patients before and after high tibial osteotomy (HTO), which represents one option for OA-treatment, as cartilage regeneration is expected after this surgery. miR-140-3p expression is significantly up-regulated 6 and 18 months post-surgery, indicating that the miR-140-3p seric level may represent a prognostic biomarker for the cartilage repair process [ 107 ].…”
Section: Role Of Mir-140-5p/-3p In Osteoarthritismentioning
confidence: 99%
“…Existing literature has demonstrated that lncRNA H19 competitively binds to miR-454-3p and other miRNAs and regulates their expression in colorectal carcinoma [11]. Notably, the expression of miR-454-3p was linked with various diseases and could act in crucial roles by targeting mRNAs [12][13][14]. The basic-helix-loop-helix (BHLH) protein BHLHE40 (also named BHLHB2, STRA13, DEC1, or SHARP2) was involved in numerous diseases [15,16].…”
Section: Introductionmentioning
confidence: 99%